Indirubin, an Active Component of Indigo Naturalis, Exhibits Inhibitory Effects on Leukemia Cells via Targeting HSP90AA1 and PI3K/Akt Pathway - Yao, Yuanzhi; Li, Xiaoying; Yang, Xiaoqin; Mou, Hai; Wei, Lin (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Background: This research intended to predict the active ingredients and key target genes of Indigo Naturalis in treating human chronic myeloid leukemia (CML) using network pharmacology and conduct the invitro verification. Methods: The active components of Indigo Naturalis and the corresponding targets and leukemia-associated genes were gathered through public databases. The core targets and pathways of Indigo Naturalis were predicted through protein-protein interaction (PPI) network, gene ontology (GO) function, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Next, after intersecting with leukemia-related genes, the direct core target gene of Indigo Naturalis active components was identified. Subsequently, HL-60 cells were stimulated with indirubin (IND) and then examined for cell proliferation using CCK-8 assay and cell cycle, cell apoptosis, and mitochondrial membrane potential using flow cytometry. The content of apoptosis-associated proteins (Cleaved Caspase 9, Cleaved Caspase 7, Cleaved Caspase 3, and Cleaved parp) were detected using Western blot, HSP90AA1 protein, and PI3K/Akt signaling (PI3K, p-PI3K, Akt, and p-Akt) within HL-60 cells. Results: A total of 9 active components of Indigo Naturalis were screened. The top 10 core target genes (TNF, PTGS2, RELA, MAPK14, IFNG, PPARG, NOS2, IKBKB, HSP90AA1, and NOS3) of Indigo Naturalis active components within the PPI network were identified. According to the KEGG enrichment analysis, these targets were associated with leukemia-related pathways (such as acute myeloid leukemia and CML). After intersecting with leukemia-related genes, it was found that IND participated in the most pairs of target information and was at the core of the target network; HSP90AA1 was the direct core gene of IND. Furthermore, the in-vitro cell experiments verified that IND could inhibit the proliferation, elicit G2/M-phase cell cycle arrest, enhance the apoptosis of HL-60 cells, reduce mitochondrial membrane potential, and promote apoptosis-related protein levels. Under IND treatment, HSP90AA1 overexpression notably promoted cell proliferation and inhibited apoptosis. Additionally, IND exerted tumor suppressor effects on leukemia cells by inhibiting HSP90AA1 expression. Conclusion: IND, an active component of Indigo Naturalis, could inhibit CML progression, which may be achieved via inhibiting HSP90AA1 and PI3K/Akt signaling expression levels.
Keywords: Chronic myeloid leukemia